Using Carbon-14 of dissolved organic carbon to determine groundwater ages and travel times in aquifers with low organic carbon. (January 2021) - Thomas, James M.; Hershey, Ronald L.; Fereday, Wyatt; Burr, George
Abstract: This study used dissolved organic carbon (DOC) carbon-14 ( 14 C) to determine groundwater ages that were then used to calculate groundwater travel times in southern Nevada aquifers that have low organic content. These travel times are compared with the more standard dissolved inorganic (DIC) 14 C method for determining groundwater ages and travel times. Groundwater travel times for aquifers in southern Nevada using DOC 14 C are thousands of years shorter than DIC 14 C travel times for groundwater flow outside of recharge areas along four of the five flow paths evaluated for this study. The DOC 14 C travel times range from 2, 300 to 2, 900 years (yrs) as compared to DIC 14 C travel times that range from 8, 200 to 22, 000 yrs (uncorrected ages) and 4, 700 to 19, 000 yrs (corrected ages). The DOC 14 C groundwater travel times in carbonate-rock and volcanic-rock aquifers of southern Nevada are similar to travel times determined from: (1) hydrogeologic data; (2) observations of rapid high-level tritium transport at the Nevada National Security Site; and (3) 550, 000-yr δ 18 O and δ 13 C global climate records for calcite precipitated in Devils Hole, Nevada at the end of one of the flow paths. DOC 14 C travel time calculations need to account for fewer processes than DIC 14 C for aquifers that contain little organic matter and do not have redox reactions. DOC 14 C travel-times can be calculated directly from the DOC 14 C data in these aquifers without corrections if dissolution of organic carbon and sorption and matrix diffusion of DOC 14 C onto or into the aquifer matrix is minimal. Laboratory experiments showed that little organic carbon was being leached from aquifer rocks, sorption of organic carbon ranged from 4.3% sorbed in carbonate rocks to 0.5% sorbed in volcanic rocks, and matrix diffusion coefficients were slower in lower porosity carbonate rocks (1.7 × 10 −7 cm 2 /s) than in higher porosity volcanic rocks (2.9 × 10 −7 cm 2 /s). The lack of dissolution of organic carbon in study area aquifers is also supported by the decrease in DOC along flow paths and the DOC composition of groundwater changing little as groundwater flows from recharge areas into the adjacent valleys. In contrast, DIC 14 C groundwater travel-time calculations must be corrected for complex chemical reactions and physical processes, including mineral/gas dissolution, mineral/gas precipitation/exsolution, cation exchange, and carbon isotopic exchange that can significantly change the amount of DIC 14 C in groundwater along flow paths by processes other than radioactive decay. DIC 14 C can also be affected by sorption and matrix diffusion, but these processes may, or may not, be captured in geochemical modeling of precipitation/dissolution and carbon isotopic exchange reactions. Corrected DIC 14 C ages, therefore, represent maximum ages. Highlights: Carbon-14 of dissolved organic carbon provides realistic groundwater ages. Organic carbon water ages are thousands of years younger than inorganic carbon ages. Dissolved organic carbon groundwater ages compare well with other age methods. Groundwater ages are important for water resource sustainability and climate change.